AN EVALUATION OF LIP-TOOTH RELATION DURING SMILE WITH DIFFERENT DENTAL RELATION (EVALUASI RELASI BIBIR DAN GIGI KETIKA TERSENYUM PADA KLASIFIKIFASI DENTAL YANG BERBEDA) - Rudi Satria Darwis; Badi Soerachman; Mutiara Sukma Suntana; Sam Widi Firmansyah (Fakultas Kedokteran Gigi Unjani, 2022)
A smile is a form of the human face that can increase the value of the beauty of a look. Teeth lips and supporting soft tissue will provide a beautiful and harmonious smile. There is an analytical method that works to analyze the smile parameters for the teeth and mouth of the patient. This study aims to analyze the characteristic of a smile on the smiling frontal photo compilation with Angle's malocclusion. The smile analysis of this study took a sample of 16-18 years succeeded in 81 people with 37 men and 47 women. Data was taken using adobe photoshop to measure maximum incisor exposure, slit between the mouth, width of the inner commissure. The research results showed a different value ​​both on the average and statistically significant differences in assessment among malocclusion groups for maximum incisor exposure parameters and gaps between spaces. Classification of Angle's class I, II, and III patients had different smile characteristics. DOI : 10.54052/jhds.v1n3.p259-266